Predicting visceral adipose tissue by MRI using DXA and anthropometry in adolescents and young adults - Laddu, Deepika R. (Int J Body Compos Res, 2012)
OBJECTIVE: Accumulation of intra-abdominal (visceral) adipose tissue, independent of total adiposity, is associated with development of metabolic abnormalities such as insulin resistance and type-2 diabetes in children and adults. The objective of this study was to develop prediction equations for estimating visceral adiposity (VAT) measured by magnetic resonance imaging (MRI) using anthropometric variables and measures of abdominal fat mass from DXA in adolescents and young adults. METHODS: Cross-sectional data was collected from a multiethnic population of seventy males and females, aged 12–25 years, with BMI ranging from 14.5–38.1 kg/m(2). Android (AFM; android region as defined by manufacturers instruction) and lumbar L1-L4 regional fat masses were assessed using DXA (GE Lunar Prodigy; GE Lunar Corp, Madison, WI, USA). Criterion measures of intra-abdominal visceral fat were obtained using single-slice MRI (General Electric Signa Model 5x 1.5T) and VAT area was analyzed at the level OF L4–L5. Image analysis was carried out using ZedView 3.1. RESULTS: DXA measures of AFM (r=0.76) and L1-L4 (r=0.71) were significantly (P<0.0001) correlated with MRI-measured VAT. DXA AFM, together with gender and weight, explained 62% of the variance in VAT (SEE=10.06 cm(2)). DXA L1-L4 fat mass with gender explained 54% of the variance in VAT (SEE=11.08 cm(2)). Addition of the significant interaction, gender × DXA fat mass, improved prediction of VAT from AFM (R(adj)(2)=0.61, SEE=10.10cm(2)) and L1-L4 (R(adj)(2)=0.59, SEE=10.39cm(2)). CONCLUSION: These results demonstrate that VAT is accurately estimated from regional fat masses measured by DXA in adolescents and young adults.